The surface of dog articular cartilage: a scanning electron microscope study. - Ghadially, F N (1977)
The surface of dog articular cartilage attached to subchondral bone shows many humps on its surface when examined with the scanning electron microscope. The situation here contrasts with that in man and rabbit where large numbers of pits are seen of the surface. Such species variations cast doubts on the idea that pits and humps play a vital role in joint mechanics and lubrication. Ridges and undulations were not found in normal dog cartilage attached to bone, but complex systems of ridges did develop when the cartilage was cut or detached from bone.